Comparative effectiveness and safety of insulin reference biologics versus biosimilars for types 1 and 2 diabetes mellitus: Protocol for a systematic review of real-world studies - Martin K. H. Ho; Araniy Santhireswaran; Tara Gomes; Muhammad Mamdani; Mina Tadrous (PLoS ONE, 2025)
Introduction Diabetes mellitus is characterized by insulin deficiency or resistance. The two main types of diabetes mellitus are type 1 (T1DM) and type 2 (T2DM). Insulin is the mainstay of therapy for T1DM and often the last-line therapy for T2DM. Biosimilar insulins are cost-saving alternatives to reference products that may improve access for patients and sustainability for healthcare systems. Despite supporting evidence from randomized controlled trials, biosimilar insulin uptake is poor, and real-world evidence of their safety and effectiveness is limited. Objective Our objective is to compare the real-world effectiveness and safety of insulin biosimilars versus reference products in adults with diabetes mellitus. Eligibility criteria We will include observational studies and open-label pragmatic randomized controlled trials. We will exclude other randomized controlled trials, literature reviews, meta-analyses, case series, case reports, study protocols, opinion pieces, and conference abstracts. Our primary effectiveness outcome will be glycated hemoglobin (HbA1c) and our primary safety outcome will be hypoglycemia. Our secondary outcomes will include fasting plasma glucose; time in range; microvascular complications; health-related quality of life; physician visits, emergency department visits, and hospital admissions for hypoglycemia, hyperglycemia, and diabetic ketoacidosis; weight gain; immunogenicity; injection site reactions; and incident cancers. Methods The search strategy combines three key concepts: diabetes, insulin, and biosimilars. We will conduct a structured search in MEDLINE, EMBASE, and International Pharmaceutical Abstracts. We will also search in grey literature databases, targeted websites, and the Google search engine. Finally, we will scan forward and backward citations. Articles will be screened, extracted, and appraised independently by two reviewers. Data will be descriptively summarized. Discussion Our systematic review of the real-world evidence on biosimilar insulins can help support clinical and policy decisions that impact the care of patients with T1DM or T2DM.